Non-catalytic-Region Mutations Conferring Transition of Class A β-Lactamases Into ESBLs - Cao, Thinh-Phat; Yi, Hyojeong; Dhanasingh, Immanuel; Ghosh, Suparna; Choi, Jin Myung; Lee, Kun Ho; Ryu, Seol; Kim, Heenam Stanley; Lee, Sung Haeng (Frontiers in Molecular Biosciences, 2020)
Despite class A ESBLs carrying substitutions outside catalytic regions, such as Cys69Tyr or Asn136Asp, have emerged as new clinical threats, the molecular mechanisms underlying their acquired antibiotics-hydrolytic activity remains unclear. We discovered that this non-catalytic-region (NCR) mutations induce significant dislocation of β3-β4 strands, conformational changes in critical residues associated with ligand binding to the lid domain, dynamic fluctuation of Ω-loop and β3-β4 elements. Such structural changes increase catalytic regions’ flexibility, enlarge active site, and thereby accommodate third-generation cephalosporin antibiotics, ceftazidime (CAZ). Notably, the electrostatic property around the oxyanion hole of Cys69Tyr ESBL is significantly changed, resulting in possible additional stabilization of the acyl-enzyme intermediate. Interestingly, the NCR mutations are as effective for antibiotic resistance by altering the structure and dynamics in regions mediating substrate recognition and binding as single amino-acid substitutions in the catalytic region of the canonical ESBLs. We believe that our findings are crucial in developing successful therapeutic strategies against diverse class A ESBLs, including the new NCR-ESBLs.